Kajian Awal Potensi Penyerapan Karbon oleh Hutan Kota Cipayung dan Munjul di Jakarta Timur - Tambunan, Renaldi Bahri; Effendi, Yunus; Wasitaatmadja, Fokky Fuad (Universitas Al Azhar Indonesia, 2025)
Urban forests hold potential as carbon sinks while also providing vital ecosystem services. This study aims to analyze the carbon sequestration potential of Cipayung and Munjul Urban Forests in East Jakarta and to offer policy recommendations for the Jakarta Provincial Government. Field measurements were conducted using Diameter at Breast Height (DBH) data, which were collected through stratified random plot sampling. Biomass was estimated using the IPCC (2006) allometric equation, combined with species-specific wood density values. The results show that Cipayung Urban Forest sequesters approximately 111.52 tons CO₂ eq, while Munjul Urban Forest sequesters 42.10 tons CO₂ eq. These differences are influenced by vegetation structure and species composition. Ecologically, urban forests contribute to local greenhouse gas reduction while supporting adaptation to extreme weather, including reducing urban temperature and improving water absorption capacity. Policy implications include the need for the Jakarta Provincial Government to strengthen urban forest protection regulations, integrate urban forests into spatial planning, and enhance participatory community-based management. The limitation of this study lies in its coverage, which was restricted to only two urban forests; therefore, future studies should expand to other urban green areas across Jakarta.Keywords - Carbon Sequestration, Jakarta, Urban Forest.